2018
DOI: 10.3892/ol.2018.9586
|View full text |Cite
|
Sign up to set email alerts
|

Association between circadian and chemotherapeutic cycle effects on plasma concentration of 5‑fluorouracil and the clinical outcome following definitive 5‑fluorouracil/cisplatin‑based chemoradiotherapy in patients with esophageal squamous cell carcinoma

Abstract: Therapeutic drug monitoring (TDM) of 5-fluorouracil (5-FU) is believed to be a clinical option for improving clinical responses. Evaluating the potential factors contributing to plasma 5-FU concentration is important to develop TDM of 5-FU. Our aim was to evaluate the association of the circadian and treatment cycle effects on plasma 5-FU concentration with the clinical response. A post hoc population analysis was performed using the plasma concentration of 5-FU and clinical response data, including prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Because of the short half-life of 5-FU (10-15 minutes), the C ss of the samples are suggested to be taken at least 18 hr after the start of 5-FU infusion (9,10). 5-FU infusion started at the same time for all patient and plasma samples were collected near the same time of the day after starting infusion to eliminate circadian changes in 5-FU metabolism (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the short half-life of 5-FU (10-15 minutes), the C ss of the samples are suggested to be taken at least 18 hr after the start of 5-FU infusion (9,10). 5-FU infusion started at the same time for all patient and plasma samples were collected near the same time of the day after starting infusion to eliminate circadian changes in 5-FU metabolism (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using population model analysis in oesophageal squamous cell carcinoma patients receiving an 5FU IV infusion over 5 days, plasma 5FU concentrations were observed to be higher in the evening compared to the morning. The authors reported that circadian variations in 5FU plasma concentration during continuous infusion was relatively small and did not contribute to clinical response or toxicity 17 …”
Section: The Clinical Challenges In Dosingmentioning
confidence: 99%
“…##DPYD variants screening is being used in routine clinical practice for both 5FU and capecitabine variations in 5FU plasma concentration during continuous infusion was relatively small and did not contribute to clinical response or toxicity. 17 Inhibition of DPD activity by coadministered drugs will also affect 5FU pharmacokinetics. Fatalities due to DPD inhibition occurred when the antiviral drug sorivudine was coadministered with 5FU.…”
Section: The Clinical Challenges In Dosingmentioning
confidence: 99%
“…However, the proper identification of covariates influencing 5FU PK would be crucial for such models. So far, published 5FU models could only include a very heterogenous set of covariates [89,[92][93][94][173][174][175][176]. Particularly, DPYD genotypes could not be successfully implemented.…”
Section: Markov Model Of Patient-reported Hand-foot Syndrome Under Ca...mentioning
confidence: 99%